Research on the dynamic characteristics and disaster mechanism of anti-slide short pile-supported slopes - Yuan Liu; Jie Lai; Yun Liu (Scientific Reports)
Abstract The terrain in Southwest China is predominantly mountainous with many slopes requiring reinforcement. This region also experiences frequent rainfall and earthquakes, which can trigger landslides. Therefore, studies on slope reinforcement are crucial. In this study, we present a case study of a slope stabilization project along the Yunyang–Fengjie Expressway in Chongqing, focusing on the seismic performance of anti-slide short pile-supported slopes. By inputting the Wenchuan earthquake wave and gradually increasing the amplitude of the seismic wave, we examined the failure evolution process of an anti-slide short pile-supported slope. The experiments revealed that the failure mode of the slope comprised tensile and shear components, with tensile cracks occurring at the crest, and shear cracks developing in the remaining fractured sections. The anti-slide short piles effectively redirected the downward extension of shear cracks. As the seismic activity intensified, shear cracks propagated along the weak interlayer towards the toe of the slope. When the cracks approached the intersection of the anti-slide short piles and weak interlayer, they were impeded by the piles, altering their development path along the weak interlayer. This change caused the cracks to extend towards the top of the anti-slide piles, ultimately causing overall failure. The bending moment of the anti-slide piles under the seismic action primarily followed a parabolic shape, with the maximum value occurring near the weak interlayer.